Bioaffinity ultrafiltration coupled with HPLC-ESI-MS/MS for screening potential α-glucosidase inhibitors from pomegranate peel - Shi, Rujie; Zhou, Nong; Zhang, Han; Gong, Min; Han, Lin (Frontiers in Nutrition, 2022)
Pomegranate peel (PoP) contains plenty of bioactive compounds and exhibits strong activity to prevent postprandial hyperglycaemia and improve diabetes mellitus. Presently, bioaffinity ultrafiltration coupled with HPLC-ESI-MS/MS is employed to screen and identify the efficient α-glucosidase inhibitors in PoP and the detailed inhibitory mechanisms are further investigated. The results show that many substances in PoP reveal strong activity to inhibit α-glucosidase and ellagic acid (EA) is screened as the most effective compound. Further research indicates that EA plays a competitive and reversible inhibition role against α-glucosidase with the value of Ki was 6.24×105 mol/L. EA also directly interacts with the amino acids of α-glucosidase mainly via van der Waals forces and hydrogen bonds, thereby, influencing the secondary structure and stability of α-glucosidase. Finally, the α-glucosidase inhibitory activity of EA is further confirmed to significantly reduce postprandial blood glucose in vivo.